PENGARUH PEMBERIAN VITAMIN B KOMPLEKS PADA IBU MENYUSUI TERHADAP KUALITAS AIR SUSU IBU (ASI) - Djoko Kartono; Suhartato Suhartato; Sudjasmin Sudjasmin (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 1998)
Deficiency in vitamin B complex during lactating period results in low level of the vitamins in the breast milk. In severe deficiency it can cause biochemical changes lead to development and growth retardation especially among exclusive breast feeding infant. A study was conducted in subdistrict Ciomas, district of Bogor amongst 73 lactating mothers of 0-5 months infants. They were grouped into treatment group (39) and control group (34). The treatment group received vitamin B complex contained 6 mg of vitamin B1, 6.5 mcg of vitamin B12 and 500 mcg of folic acid every day for three months and no intervention for control group. The dosage was five times higher than the recommended allowance for vitamin B1 and B12 and just in the recommended level for folic acid for lactating mothers of 0-6 month old infant. The aimed of this study was to know its effect on the breast milk composition, nutritional status and food consumption pattern of the mothers and their infant. There was no significant improvement in the level of vitamin B1, B12 and folic acid as the effect of the intervention. The level of vitamin B1 in breast milk was adequate for the infant based on the recommended allowance level for lactating mothers of 0-4 months exclusive breast feeding infant but not for vitamins B12 and folid acid. These results suggest either the dose is too low of the duration of supplementation too short. Keywords: supplementation, vitamin B complex, lactating mother, breast milk